2021
DOI: 10.1038/s41598-021-86425-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of microbiome in Chronic Fatigue Syndrome/Myalgic Encephalomyelits (CFS/ME)

Abstract: Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) is a severe multisystemic disease characterized by immunological abnormalities and dysfunction of energy metabolism. Recent evidences suggest strong correlations between dysbiosis and pathological condition. The present research explored the composition of the intestinal and oral microbiota in CFS/ME patients as compared to healthy controls. The fecal metabolomic profile of a subgroup of CFS/ME patients was also compared with the one of healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 90 publications
5
45
0
1
Order By: Relevance
“…In particular, a decrease in microbial diversity and a drop in Firmicutes number was found in CFS patients compared to controls [ 137 ]. Moreover, other studies confirmed a reduction in Bacteroidetes/Firmicutes ratio and an increase in Enterobacteriaceae, thus providing evidence of a complete reorganization in intestinal microbiome composition and function [ 139 , 140 ]. The use of microbiota alteration as a diagnostic biomarker has also been suggested, but disease overlap with other intestinal disorders may represent a disturbing factor during diagnosis and patient stratification [ 138 ].…”
Section: Resultsmentioning
confidence: 86%
“…In particular, a decrease in microbial diversity and a drop in Firmicutes number was found in CFS patients compared to controls [ 137 ]. Moreover, other studies confirmed a reduction in Bacteroidetes/Firmicutes ratio and an increase in Enterobacteriaceae, thus providing evidence of a complete reorganization in intestinal microbiome composition and function [ 139 , 140 ]. The use of microbiota alteration as a diagnostic biomarker has also been suggested, but disease overlap with other intestinal disorders may represent a disturbing factor during diagnosis and patient stratification [ 138 ].…”
Section: Resultsmentioning
confidence: 86%
“…Significant dysregulations in the overall composition of microbiota and shifted ratios between several bacterial taxa in comparison to healthy controls have been detected ([ 61 , 62 ], Figure 1 , Table 1 ). For example, a modified microbiome was found in saliva, gut, and feces of ME/CFS cases, linking the GM to the disease [ 12 , 63 ]. Moreover, when 16S ribosomal ribonucleic acid (rRNA) sequencing was used to compare stool samples from 43 ME/CFS individuals and 36 healthy controls, an altered GM composition and imbalance in microbial diversity have been reported ([ 64 ] Table 1 ).…”
Section: Main Findingsmentioning
confidence: 99%
“…It is important to note that the severity of FF symptoms in ME/CFS is significantly associated with signs of immune activation including increased levels of pro-inflammatory cytokines, elastase, and lysozyme, oxidative damage, hypernitrosylation, mitrochondrial disorders, and changes in the gut-brain axis (Maes and Twisk, 2010; Maes et al, 2012; Morris and Maes, 2014a; Hornig et al, 2017; Bjorklund et al, 2020; Strawbridge et al, 2019; Nagy-Szakal et al, 2017; Anderson and Maes, 2020; Lupo et al, 2021). There is also some evidence that fibromyalgia is accompanied by immune activation as reviewed in a recent meta-analysis, which showed increased IL-6, IL-17, and IL-4 levels, and increased M1 and T regulatory profiles, although the effect sizes were very modest (Andrés-Rodríguez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%